ANALISIS PENGARUH DAYA, TINGKAT KEBISINGAN, DAN TORSI SEPEDA MOTOR 4 TAK PADA PENGGUNAAN KNALPOT DENGAN BUSI RACING DAN MODEL FREE FLOW - Ridho Akhya; Husin Bugis; Basori Basori (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The objective of this study to specify the effect of the use of model variation free flow exhaust and spark plug racing against torque, power and the noise level generated. This research is descriptive quantitative experimental method. The sample used is the Supra X motorcycle 125d which uses exhaust components and the plugs are standard. Data obtained from the measurement of torque, power and noise levels using a tool Sportdyno V3.3 and Sound Level Meter to perform replacement treatment models as well as the free flow exhaust racing spark plugs compared to standard conditions. The research show that use of exhaust and spark plugs have signification variations were tested. Of all the test results obtained torque decreases from all experimental treatments. Lowering the lowest torque obtained on the use variations of free flow exhaust and spark plug racing. At the same usage also generated the increase in power and the noise level of the most significant.